UMP residents celebrate Aidilfitri, appreciate frontliners - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 24 May 2022 - The university highly appreciated the tireless sacrifice of frontliners at Universiti Malaysia Pahang (UMP) to curb the spread of the COVID-19 pandemic among campus residents.